Rancang Bangun Sistem Aplikasi Penilaian Kinerja Karyawan Berbasis Web pada RSI Jemursari Surabaya - Paramastri, Raras Dhika; Setyawan, Henry Bambang; Erstiawan, Martinus Sony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Islamic Hospital (RSI) Jemursari Surabaya is a hospital that serves all segments of society, religion, and socio-economic levels. Employee performance appraisal is one process for determining the quality of human resources (HR) at the RSI Jemursari Surabaya. During this time the performance appraisal conducted in RSI Jemursari Surabaya still uses such assessment form sheets of paper so that it can slow down the process of employee performance evaluation and wasteful use of paper. Based on the above problems, it needs to be made web-based application that can handle the performance appraisal process. This web-based application used by three users, namely employee, boss Employees and HR Department. In the assessment of applications, there are several processes, namely the process of making master criteria for performance and master type of violation, the employee performance appraisal process (co-employee, myself, and subordinates), and the process of making the performance appraisal report. Based on the results of trials that have been done with the RSI Jemursari Surabaya then this app may conduct performance appraisals for employees coworkers, yourself, and the subordinate employee. This application can also generate the value of employee performance and employee supervisor recommendations regarding the results of the performance appraisal to the trainee employees, first contract employees, second contract employees and permanent employees. Application performance appraisal may be expanded by the addition means such assessment checklist, an essay, or a recording of critical events and can be developed into a system that is integrated with a presence system and payroll system.